Theoretical study on design methods for pinned assembled BRB with flat core. (15th February 2017) - Jiang, Z.Q.; Dou, C.; Guo, Y.L.; Zhang, A.L.
Highlights: The stress state of BRB with multi-wave deformation is deduced, and verified by FEA. A design method applicable for the pinned ABRB with a flat core is put forward. The stiffness reduction coefficient of the external restraining is considered. The local stress of the ABRBs' external member caused by core contact force is given. Abstract: The external restraining members in an Assembled Buckling-Restrained Brace (ABRB) are mainly connected by high-strength bolts. Because of the bolts' longitudinal discrete layout, the stiffness reduction of the external restraining members should be considered, and a significant increase in the local stress of the external member between two bolts must be considered as well. Thus, this study first uses theoretical derivation and numerical verification to investigate the stress state of BRB subjected to core single-wave overall deformation and core multi-wave buckling deformation, respectively. Based on the unique mechanical characteristics of the pinned ABRBs, a design method applicable for the pinned ABRB with a flat core is put forward, considering the external restraining stiffness reduction coefficient and the additional local influence of contact force when the core deforms in a multi-wave form. Finally, six ABRB FE models are presented to verify the rationality of the design method being safe and reliable to predict the ABRB's overall buckling failure and bending failure in the ECSR of BRBs. This design method also considers the influence of a series of design parameters, including the gap between the core and external members, pinned connector length, extended core length, length, strength, stiffness and imperfection of the external restraining members, bolt dimensions and layout, etc.